Σύνθετη εικόνα της αγίας Παρασκευής με σκηνές του βίου της στο Εκκλησιαστικό Μουσείο της Σιάτιστας - Παπαδημητρίου, Παρασκευή Χ. (Μακεδονικά, 2011)
In the Ecclesiastical Museum of Siatista a «complex» icon is found withten scenes from the life of saint Paraskevi the Roman (fig. 1) in the centre ofwhich, after taking off the central panel, a more recent icon has been fitted inwith saint Paraskevi of Ikonio, in full length (fig. 2).Special interest appears in the fact that the added central icon and thatwith scenes from her life, depict a different saint Paraskevi. The palaeoslavonic inscriptions and the iconographic type of the saint in the central iconleave no doubt that it is about a depiction of saint Paraskevi of Ikonio. On thecontrary, the greek inscriptions and the particular incidents historiated on theframe of the older icon (although the artist doesn’t follow the historic narration faithfully) clearly indicate that it is about saint Paraskevi the Roman.There has been special reference in certain scenes of the frame, whichare scarce in the iconography of saint Paraskevi the Roman, such as the torture of the saint, which is hung by the hair, the apparition of Jesus Christ withthe angels in her prison, as well as her prayer before her decapitation. In fact,these scenes are attributed mainly to icons which are dated after the 17th century.Technical and stylistic elements indicate that the artist who painted theicon of the Ecclesiastical Museum of Siatista belongs to the north-greekschool of painting of the early 17th century. The added central icon with saintParaskevi of Ikonio nevertheless belongs to a Russian artist and is dated inthe 18th century